2021
DOI: 10.3389/fpsyg.2021.685756
|View full text |Cite
|
Sign up to set email alerts
|

STOP SHOUTING AT ME: The Influence of Case and Self-Referencing on Explicit and Implicit Memory

Abstract: Evidence suggests that physical changes in word appearance, such as those written in all capital letters, and the use of effective encoding strategies, such as self-referential processing, improves memory. In this study we examined the extent both physical changes in word appearance (case) and encoding strategies engaged at study influence memory as measured by both explicit and implicit memory measures. Participants studied words written in upper and lower case under three encoding conditions (self-reference,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Thus, it may be that our finding of a prosocial advantage in memory where participant remember specific details (impressions; behaviors) associated with targets, may be adaptive and help guide future goal-directed behaviors in social contexts. Examining conditions under which memory might be improved is an important pursuit (Bjork & Benjamin, 2011;Burden et al, 2021;Frankenstein et al, 2022;Ilenikhena et al, 2021;Leach et al, 2019;, 2014Leshikar et al, , 2017Matzen et al, 2015), and the results of the current investigation contribute to that empirical goal.…”
Section: In Addition To Finding Improved Impression Memory For Targetsmentioning
confidence: 87%
“…Thus, it may be that our finding of a prosocial advantage in memory where participant remember specific details (impressions; behaviors) associated with targets, may be adaptive and help guide future goal-directed behaviors in social contexts. Examining conditions under which memory might be improved is an important pursuit (Bjork & Benjamin, 2011;Burden et al, 2021;Frankenstein et al, 2022;Ilenikhena et al, 2021;Leach et al, 2019;, 2014Leshikar et al, , 2017Matzen et al, 2015), and the results of the current investigation contribute to that empirical goal.…”
Section: In Addition To Finding Improved Impression Memory For Targetsmentioning
confidence: 87%
“…In addition to improved item memory for lower versus higher constraint conditions, we also found that item memory was better for items processed in both testing conditions (lower, higher constraint) compared to controls (restudy, study‐only), which is consistent with a vast literature showing that testing (or retrieval practice) improves item memory (Adesope et al., 2017 ; Glover, 1989 ; Roediger & Karpicke, 2006 ; Rowland, 2014 ). Finding ways to improve memory is an important scientific endeavor (Bjork & Bjork, 2011 ; Burden et al., 2021 ; Frankenstein et al., 2020 , 2022 ; Ilenikhena et al., 2021 ; Kadwe et al., 2022 ; Leshikar, In Press ; Leshikar et al., 2019 , 2017 ; Leshikar, Park, et al., 2015 ; Matzen et al., 2015 ; Patel et al., 2022 ; Sklenar et al., 2022 , 2021 , 2023 ; Udeogu et al., 2022 ; Urban Levy et al., 2023 ; Villasenor et al., 2021 ), and the results of this investigation add to that cause.…”
Section: Discussionmentioning
confidence: 99%
“…Though cognitive mechanisms have been proposed to explain the retrieval practice effect, we were interested in the extent self-efficacy, a social-cognitive factor, could contribute to this memory benefit. It is well known constructs related to one’s sense of self have a strong effect on memory (Brown et al, 1986 ; Gutchess et al, 2007 ; Ilenikhena et al, 2021 ; Leshikar et al, 2015b ; Leshikar & Duarte, 2012 , 2014 ; Rogers et al, 1977 ; Symons & Johnson, 1997 ; Wong et al, 2017 ), and past work has demonstrated a relationship between self-efficacy and memory in both laboratory and academic contexts (Beaudoin & Desrichard, 2011 ; Huang & Mayer, 2018 ; Multon et al, 1991 ; Robbins et al, 2004 ). The work we present in this investigation provides additional evidence that changes in self-efficacy is related to memory performance.…”
Section: Discussionmentioning
confidence: 99%